PERSEPSI MASYARAKAT TERHADAP PERUBAHAN DESA MENJADI KAMPUNG ADAT (DESA ADAT) DI DESA KUALA GASIB KECAMATAN KOTO GASIB KABUPATEN SIAK - lasmaria, Juliwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was conducted from the change of the village name into a traditional village earlier has been used in the village of Kuala Gasib Koto Gasib Siak District. The formulation of the study was